Identification of Rhizoctonia solani AG 1-IB in lettuce, AG 4 HG-I in tomato and melon, and AG 4 HG-III in broccoli and spinach, in Brazil - Kuramae, E. E.; Buzeto, A. L.; Ciampi, M. B.; Souza, N. L. (Kluwer Academic Publ, 2003)
Fungi isolated in Brazil, from lettuce, broccoli, spinach, melon and tomato, were identified as Rhizoctonia solani. All lettuce isolates anastomosed with both AG 1-IA and IB subgroups and all isolates from broccoli, spinach, melon and tomato anastomosed with AG 4 subgroup HG-I, as well as with subgroups HG-II and HG-III. DNA sequence analyses of ribosomal internal transcribed spacers showed that isolates from lettuce were AG 1-IB, isolates from tomato and melon were AG 4 HG-I, and isolates from broccoli and spinach were AG 4 HG-III. The tomato isolates caused stem rot symptoms, the spinach, broccoli and melon isolates caused hypocotyl and root rot symptoms on the respective host plants and the lettuce isolates caused bottom rot. This is the first report on the occurrence in Brazil of R. solani AG 4 HG-I in tomato and melon, of AG 4 HG-III in broccoli and spinach and of AG 1-IB in lettuce.
Keywords: ITS; 5.8S rDNA; Thanatephorus cucumeris; AG 1 and AG 4